METHODOLOGICAL TOOLS FOR STUDYING THE IMAGE OF “SELF-PROFESSIONAL” IN AVIATION STUDENTS - Патруль, Марія (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article summarises the scientific approaches to the study of the ‘professional self’ image and, taking into account the specific features of the professional activity of specialists in the aviation industry, selects psychological tools for further empirical research. The purpose of the study is to theoretically analyse the specific features of the formation of the ‘professional self’ image in aviation students, in particular, its components and to select diagnostic tools for further empirical research. The aim is driven by the importance of studying the ‘professional self’ image, since it significantly affects the learning process and professional self-realisation of a future specialist. A positive self-professional image promotes openness to new knowledge and development, increasing the effectiveness of learning, while a negative image can create psychological barriers and inhibit professional development. Therefore, studying this aspect is critical for the successful training of competitive aviation professionals. The research procedure involved the analysis of scientific papers, individualisation of the specifics of professional activity, generalisation of leading ideas, modelling the structure of the components of the ‘self-professional’ image of aviation students. At the level of such methodological systematicity, the components of the ‘professional self’ image of aviation students are allocated. It is emphasised that the formation of the phenomenon of the ‘professional self’ image is directly related to the content and requirements of the future profession. Based on the results of the study, psychodiagnostic tools for studying the ‘professional self’ image of aviation students were selected, which will allow a thorough study of the specifics and dynamics of its structural components (cognitive, emotional, evaluative and behavioural). The conclusions summarise the importance of conducting an empirical study using a set of psychodiagnostic techniques to investigate the ‘professional self’ image of aviation students, in particular, to identify its cognitive, emotional and behavioural components. The results obtained will allow to identify the peculiarities of formation, dynamics and gaps in the development of the image and, if necessary, will allow to propose ways, methods and means that will contribute to the uniform formation of the ‘professional self’ image during the professional training of aviation students. Key words: components, methodological tools, image of ‘I am professional’; psychodiagnostic methods, students of aviation specialities.